Reduced-State Sequence Estimation for Complementary Code Keying - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2004)
In this paper, reduced-state sequence estimation (RSSE) designed for complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. An Ungerboeck-like set partitioning of the multidimensional CCK symbol constellation is given. For the proposed RSSE algorithm based on this partitioning, numerical results are provided for a typical indoor wireless channel. A comparison is made with optimum detection and suboptimum decision-feedback equalization (DFE), respectively.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.reduce
Keywords: Complementary code keying; Reduced-state sequence estimation; Set partitioning; WLAN IEEE 802.11b